2012
DOI: 10.4236/psych.2012.312a165
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Positive Psychology on Diabetes Outcomes: A Review

Abstract: Background: Due to the intensive treatment requirements needed to maintain diabetes control, optimal diabetes outcomes can be difficult to achieve for individuals with type 1 or type 2 diabetes from childhood through adulthood. While risk factors related to individual differences in outcomes have been studied in depth, there is a growing body of research that has revealed the effects of positive personal and environmental characteristics on diabetes management and glycemic control. The goal of this review is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 76 publications
2
28
0
7
Order By: Relevance
“…15,16 While we did not appreciate any changes in the quality of life or self-management tasks based on the responses to the QoL and SMOD-A surveys, this may be due to the small sample size as the study was not powered to detect small changes. Several alternative instruments are available for studying self-efficacy 17 and self-care 18 in adolescent patients, and may be more suitable for this type of study.…”
Section: Discussionmentioning
confidence: 87%
“…15,16 While we did not appreciate any changes in the quality of life or self-management tasks based on the responses to the QoL and SMOD-A surveys, this may be due to the small sample size as the study was not powered to detect small changes. Several alternative instruments are available for studying self-efficacy 17 and self-care 18 in adolescent patients, and may be more suitable for this type of study.…”
Section: Discussionmentioning
confidence: 87%
“…Prior research has looked at the effect of depression symptoms on diabetes health care behaviors, but there are a number of psychological processes and/or emotional states that may be related to diabetes self-management. Besides self-esteem other studies have found that diabetes self-care behaviors are associated with self-efficacy, resilience, coping and family support and involvement [50]. Future studies should explore the relationship between different psychological barriers to proper diabetes management and quality of care received.…”
Section: Limitationsmentioning
confidence: 99%
“…Given the wide variability in how patients with chronic illness are able to manage their daily behaviours needed to maintain physical and mental well-being, positive psychology has provided a particularly useful framework to identify the factors that promote successful disease management. 33 …”
Section: Positive Psychologymentioning
confidence: 99%